Blocking STAT3/5 through direct or upstream kinase targeting in leukemic cutaneous T‐cell lymphoma. Issue 12 (7th November 2022) - Sorger, Helena; Dey, Saptaswa; Vieyra‐Garcia, Pablo Augusto; Pölöske, Daniel; Teufelberger, Andrea R; de Araujo, Elvin D; Sedighi, Abootaleb; Graf, Ricarda; Spiegl, Benjamin; Lazzeri, Isaac; Braun, Till; Garces de los Fayos Alonso, Ines; et al.
Abstract: Leukemic cutaneous T‐cell lymphomas (L‐CTCL) are lymphoproliferative disorders of skin‐homing mature T‐cells causing severe symptoms and high mortality through chronic inflammation, tissue destruction, and serious infections. Despite numerous genomic sequencing efforts, recurrent driver mutations have not been identified, but chromosomal losses and gains are frequent and dominant. We integrated genomic landscape analyses with innovative pharmacologic interference studies to identify key vulnerable nodes in L‐CTCL. We detected copy number gains of loci containing the STAT3/5 oncogenes in 74% ( n  = 17/23) of L‐CTCL, which correlated with the increased clonal T‐cell count in the blood. Dual inhibition of STAT3/5 using small‐molecule degraders and multi‐kinase blockers abolished L‐CTCL cell growth in vitro and ex vivo, whereby PAK kinase inhibition was specifically selective for L‐CTCL patient cells carrying STAT3/5 gains. Importantly, the PAK inhibitor FRAx597 demonstrated encouraging anti‐leukemic activity in vivo by inhibiting tumor growth and disease dissemination in intradermally xenografted mice. We conclude that STAT3/5 and PAK kinase interaction represents a new therapeutic node to be further explored in L‐CTCL. Synopsis: L‐CTCL remains a poorly understood rare T‐cell cancer entity. Frequently amplified STAT3/5 oncogenes and related kinase action relevant for T‐cell survival were identified as vulnerable nodes for targeting, thereby improving the prospects of a translatable targeted drug for L‐CTCL. Copy number gain of STAT3/5, which frequently co‐occurs with loss of STAT1 and SOCS1, contributes to increased clonal expansion in leukemic cutaneous T‐cell lymphoma. STAT3/5 can be blocked directly or indirectly, through upstream kinase inhibition, particularly involving PAK‐mediated STAT3/5 nuclear translocation. PAK kinase inhibition is selective for L‐CTCL patient cells carrying STAT3/5 gains and reduces growth of intradermally xenografted tumors. Abstract : L‐CTCL remains a poorly understood rare T‐cell cancer entity. Frequently amplified STAT3/5 oncogenes and related kinase action relevant for T‐cell survival were identified as vulnerable nodes for targeting, thereby improving the prospects of a translatable targeted drug for L‐CTCL.